Meta-Analysis Correlation between Dementia and the Risk of Mortality in COVID-19 Patients - Atin, Ulya Khoirunnisa’; Murti, Bhisma; Prasetya, Hanung (Indonesian Journal of Medicine, 2022)
Background: Dementia is a common cause of morbidity and mortality in the elderly population. The elderly have a higher risk when exposed to COVID-19, especially if they have serious medical conditions such as dementia (senility). The purpose of this study was to determine the effect of dementia on the risk of mortality in COVID-19 patients based on previous primary studies.Subject and Method: This research is a systematic review and meta-analysis study using PRISMA diagrams. The article search was conducted based on the eligibility criteria using the PICO Model. P: COVID-19 patients, I: dementia, C: no dementia, O: mortality. The articles used were from 3 databases, namely Pubmed, Google Scholar and Science Direct. The search keywords for articles were as follows: dementia AND (death OR Mortality) AND COVID-19 OR Sars-Cov-2. The inclusion criteria in this study include full text articles with cohort study designs, full text available articles, the size of the relationship used is the adjusted Odds Ratio or Risk Ratio, the year the article used is in the 2019-2022 range and the research outcome is mortality. Articles were analyzed using the Review Manager 5.3 application.Results: There are 9 articles in this study from New York, United States, Spain, Korea with 2 articles, and England with 4 articles. The article was analyzed using the PRISMA flow diagram. The results of the study show that COVID-19 patients with dementia have a mortality risk of 2.02 times greater than COVID-19 patients without dementia. These results were statistically significant (aOR= 2.19; 95% CI = 1.48 to 2.75; p<0.001).Conclusion: Dementia increases the risk of mortality from COVID-19Keywords: Dementia, mortality, COVID-19, SARS-COV-2Correspondence: Ulya Khoirunnisa’ Atin. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: ulyakhns9@gmail.com. Mobile: +62823259186864.Indonesian Journal of Medicine (2022), 07(03): 251-261https://doi.org/10.26911/theijmed.2022.07.03.01